METHODS OF USING COMPUTER GRAPHICS IN THE EDUCATIONAL PROCESS USING ADOBE FLASH (Conference Zone, 2022)
The use of this method in working with students in groups and in groups also guarantees positive results. The following steps are used to use this method: - The teacher prepares a special set of cards, which serve to illuminate the essence of the subject in a logical sequence (on the back of each card is placed one letter of the concept of "core" that illuminates the essence of the topic and covered with a special coating); - Each group is given a separate set of special cards and is tasked to place the cards in a logical sequence based on the concepts in them; - When the task is completed by the groups, the back of the cards is turned over and a special cover is opened to determine the correctness of the task.